Pengaruh Pendidikan Kesehatan Reproduksi terhadap Remaja Tentang Kesiapsiagaan Ketika Terjadi Bencana di Wilayah Kerja Puskesmas Pantoloan - Elvaria Mantao; Nurhaya S. Patui; Novi Inriyanny Suwendro; Rahma Dwi Larasati; Nurbaya, Nurbaya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The Pantoloan Community Health Center (Puskesmas) in Palu City was severely affected by the 2018 earthquake and tsunami. The resulting damage to many health facilities limited access to vital reproductive health services. Furthermore, significant gaps persisted in adolescents' knowledge and understanding of how to maintain their reproductive health during emergency situations.This quantitative study was designed to evaluate the effectiveness of reproductive health education in improving adolescent disaster preparedness. The research employed a quasi-experimental design using the Pretest-Posttest Group Design method. The target population consisted of all Middle Adolescents (aged 13-18 years) residing in the Pantoloan Community Health Center area, totaling approximately 561 individuals.Cluster Random Sampling was used as the sampling technique, with clusters established at each adolescent health post (Posyandu). The final sample size was 68 adolescents.Data analysis included univariate and bivariate methods. Statistical tests used were the independent sample t-test if data were normally distributed, and the Wilcoxon test if data were not normally distributed.The study results indicated a difference in the average adolescent knowledge, with an average increase of 1.93 following the provision of reproductive health education. Similarly, the average preparedness of adolescents showed a difference, with an average increase of 3.96 after the education.The statistical test results revealed that the p-value for both the knowledge and preparedness variables was 0.000. Based on these findings, it is concluded that reproductive health education is effective in increasing adolescent knowledge and preparedness for when disasters occur in the Pantoloan Community Health Center Working Area.